IMPACT OF STRUCTURED ASSIGNMENTS ON THE DEVELOPMENT OF STUDENTS' RESEARCH SKILLS - Zykrina, С. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2023)
For the development of mathematical literacy and research skills of students, it is very important to understand the information contained in the text of the problem, analyze it, and be able to structure the stages of solving the problem. In this regard, the purpose and objectives of this study were determined. The purpose of the study is to evaluate the impact of structured tasks on the development of students' skills in analyzing and systematizing information. In developing research skills, the method of preparing structured problems was chosen from a variety of methods and tools. In the process of compiling tasks structured in accordance with the research hypothesis, students get the opportunity to systematize information by step-by-step search for the necessary information. And involving students in independent structuring of tasks develops their information analysis skills. To achieve the goal of the study, the following research tasks were identified: - assessment of the effect of using methods aimed at developing research skills; - conducting a series of classes and qualitative analysis of students' knowledge; - development of proposals for organizing the activities of teachers to develop the skills of analyzing and systematizing information. During the study, studies conducted in this direction were analyzed, and a list of methods was determined that are considered prerequisites for developing skills in analyzing and systematizing information. A classification of structured tasks has been prepared and used in practice.